Production Guide of Vegetable Amaranth for Florida - Yuheng Qiu; Guodong Liu (EDIS)
Vegetable amaranth is a beautiful and nutritious vegetable in the family Amaranthaceae. This vegetable has been cultivated in China for more than 400 years and has been introduced to several US states, such as Mississippi and Missouri. Florida's mild climate combined with amaranth's exceptional taste, nutrients, and colorful foliage suggest amaranth is a potential crop for commercial production for Florida. This new 7-page publication of the UF/IFAS Horticultural Sciences Department is intended to provide Florida growers with a production guide for vegetable amaranth to enhance its competitiveness and boost the economy by introducing this potential cash crop to growers. Written by Yuheng Qiu and Guodong Liu. https://edis.ifas.ufl.edu/hs1407